Global positioning system anti-jamming algorithm based on period repetitive CLEAN - Lu, Dan; Wu, Renbiao; Liu, Haitao (IET radar, sonar & navigation, 2013)
A two-stage blind adaptive anti-jamming algorithm for global positioning systems (GPS) is proposed in this study. The new algorithm cancels interferences by projecting the array received signals on the orthogonal complement space of interferences. Then the algorithm utilises the CLEAN method to estimate direction of arrivals  of GPS signals according to the period repetitive feature of GPS coarse/acquisition (C/A) code and form the multi-beam, where each beam can point one GPS signal. Test data and simulation results show the effectiveness of the new algorithm.